2010
DOI: 10.2478/v10187-010-0050-3
|View full text |Cite
|
Sign up to set email alerts
|

Semiconducting Organic Molecular Materials

Abstract: This feature article gives an overview of recent advances in development of high performance molecular organic semiconductors for field-effect transistors with emphasis on the structure of molecular materials and requirements for highperformance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…5.1 eV below the vacuum level for Au. On the other hand, n-type dopants have a LUMO energy level between ca 3.0 and 4.0 eV (Filo and Putala, 2010). For selected small p-type molecules, the gas-phase HOMO energies ranged from -4.65 to -5.60 eV and the LUMO energy levels are between -1.12 and -3.57 eV (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…5.1 eV below the vacuum level for Au. On the other hand, n-type dopants have a LUMO energy level between ca 3.0 and 4.0 eV (Filo and Putala, 2010). For selected small p-type molecules, the gas-phase HOMO energies ranged from -4.65 to -5.60 eV and the LUMO energy levels are between -1.12 and -3.57 eV (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The efficient charge transport is mainly attributed to π-system extending with strong intermolecular overlaps. The optimal interval of energy level of the highest occupied orbitals for typical p-type semiconducting molecules is from 4.9 to 5.5 eV (Filo and Putala, 2010), because standard metallic hole injecting electrodes have comparable ionisation potentials, e.g. 5.1 eV below the vacuum level for Au.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Modern chemistry offers a wide range of possibilities to tune the electronic structure, such as Highest Occupied Molecular Orbital (HOMO) or Lowest Unoccupied Molecular Orbital (LUMO) energy levels of organic semiconducting materials (Brütting, 2005). Specifi cally, we can mention the introduction of strongly electronegative fl uorine atoms to lower the LUMOs (Filo and Putala, 2010). The measurements of Liang et al (Liang et al, 2010) showed that -defi cient fl uorinated 6,13-pentacenequinones and corresponding N-heteropentacenequinones can work as chemically stable n-type organic semiconductors in thin fi lm transistors with the electron mobility up to 0.1 cm 2 V -1 s −1 .…”
Section: Introductionmentioning
confidence: 99%